Satire or Send-Up? Paddy Power and Blind Football : A Case for Managing Public Relations for Disability Sport - de Haan, Donna and Osborne, Angela and Sherry, Emma (Communication & Sport, 2015)
In 2010, a television advertisement aired in the lead up to the 2010 World Blind Football Championships featuring the English Blind Football Team and a cat became the most controversial advert of the year. This article uses a case study approach to examine the public relations (PR) and communications activities that followed in the fallout from the advert’s broadcast. It shows how the sport organisation’s approach to PR can be characterised by a symbolic interaction approach to PR, developed post hoc, and concerned with creating a favourable impression of the organisation through the manipulation of messaging and argues that this method had questionable ameliorative impact. It further argues that for a niche sport, a more appropriate approach to PR is found in a relationship management approach to PR and communications, as this approach embeds PR at a strategic level and is an effective method for organisations seeking to take strategic control of the communications about their sport. The adoption of strategic relationship management principles to PR offers opportunities to engender a more sophisticated public understanding of disability in sport, increase its popularity, and ensure that elite athletes with a disability are able to attract sponsors and vital funds.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8yMTY3NDc5NTEzNTE4MDQ1